Answer:
Option a.
![\lim_{x \to (\pi)/(2)}(3e)^(xcosx)=1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/2zt2ziokwrzwxggl0dgxzrp9kz7lv01jkf.png)
Explanation:
You have the following limit:
![\lim_{x \to (\pi)/(2){(3e)^(xcosx)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/91jrfo7jrcwemzcfrrz6455gbjlsiqhzmi.png)
The method of direct substitution consists of substituting the value of
in the function and simplifying the expression obtained.
We then use this method to solve the limit by doing
![x=(\pi)/(2)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/rw8xj1186yi6rzclexmzi10ftzfy7kgubm.png)
Therefore:
![\lim_{x \to (\pi)/(2)}{(3e)^(xcosx) = \lim_{x\to (\pi)/(2)}{(3e)^{(\pi)/(2)cos((\pi)/(2))}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/t3k6vfzg2x087pk33tzkf32ozezbqwxcvy.png)
![cos((\pi)/(2))=0\\](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ikbxzjfnt6pt7f9f1vh78hive1mppadxgv.png)
By definition, any number raised to exponent 0 is equal to 1
So
![\lim_{x\to (\pi)/(2)}{(3e)^{(\pi)/(2)cos((\pi)/(2))} = \lim_{x\to (\pi)/(2)}{(3e)^{(\pi)/(2)(0)}\\\\](https://img.qammunity.org/2020/formulas/mathematics/middle-school/5psqs637v6ih18v82ehsmpkm60co18ajx8.png)
![\lim_{x\to (\pi)/(2)}{(3e)^(0)} = 1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/n0mz7oyxhknap92e9h6zjnvwob5dy2irn8.png)
Finally
![\lim_{x \to (\pi)/(2)}(3e)^(xcosx)=1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/2zt2ziokwrzwxggl0dgxzrp9kz7lv01jkf.png)